Regional origins of employment volatility: evidence from German states - Claudia M. Buch; Martin Schlotter (Center for Economic Studies and ifo Institute (CESifo), 2008)
Openness for trade can have positive welfare effects in terms of higher growth. But increased openness may also increase uncertainty through a higher volatility of employment. We use regional data from Germany to test whether openness for trade has an impact on volatility. We find a downward trend in the unconditional volatility of employment, which has been interrupted by the re-unification period. Patterns are similar to those for output volatility. The conditional volatility of employment, measuring idiosyncratic developments across states, in contrast, has remained fairly unchanged. In contrast to evidence for the US, we do not find evidence for a significant link between employment volatility and trade openness.
Keywords: F41; E32; R23; 330; employment volatility; trade openness; regional labour markets; Politik der offenen Tür; Regionaler Arbeitsmarkt; Beschäftigungseffekt; Volatilität; Offene Volkswirtschaft; Deutschland